Avaliação do envolvimento da via de sinalização PKA na nefrotoxicidade causada pela Anfotericina B e Ciclosporina utilizando linhagens celulares LLC-PK1 e MDCK - Flavia Dayrell França (2013)
Amphotericin B (antifungal) and Cyclosporine (immunosuppressant) are commonly used drugs in medical clinics; however, these often present Nephrotoxicity. The proposal of the present study was to evaluate the involvement of the cellular PKA signaling pathway on Nephrotoxicity caused by Amphotericin B and Cyclosporine using renal cell lines: LLC-PK1 (proximal tubules of pigs) and MDCK (distal tubules of dogs). To accomplish this goal, the present study evaluated parameters involved in Nephrotoxicity, such as cytotoxicity (Neutral Red and MTT), cell death (Flow Cytometry), the recovery of toxic effects (Neutral Red), inflammatory cytokine quantification, the vasodilator effect (quantification of nitric oxide), and the participation of PKA (Western Blot). The results showed that both drugs, when evaluated by neutral Red and MTT tests, proved to be cytotoxic to both cell lines, and when evaluated by Flow Cytometry using Propidium iodide, they caused DNA fragmentation. The two cell lines were able to recover from the toxic effect caused by Amphotericin B and Cyclosporine, but the recovery times varied, depending on the drugs and cell lines used. In the analysis of the involvement of the PKA signaling pathway on Nephrotoxicity caused by these drugs, when cells were pre-treated with H89 (PKA inhibitor) and then with the drugs, no significant difference between the groups, when evaluated by Neutral Red, could be observed. When the same analysis was performed using Flow Cytometry in MDCK, the inhibition of the PKA pathway decreased the percentage of cell death caused by Amphotericin B and Cyclosporine. Inhibition of the pathway did not affect the capacity of cell recovery in either of the two cell lines. When the production of pro-inflammatory cytokines was evaluated as regards the nephrotoxic process, it could be observed that Amphotericin B stimulated the production of IL-6, which proved to be dependent on the PKA pathway, whereas Cyclosporine did not alter the production of this cytokine. In relation to TNF-, both drugs stimulated this production; however, the inhibition of the PKA pathway did not alter this production. Both drugs caused a decrease in the production of Nitric Oxide (vasodilator substance), and this production proved to be dependent on the PKA pathway. Western Blot results confirmed that both drugs induce the activation of the PKA pathway. Thus, the present studys results suggest that the inhibition of the PKA pathway can aid in preventing/reducing Nephrotoxicity caused by Amphotericin B and Cyclosporine.